PENERAPAN TEKNOLOGI NANOMEDISIN DALAM PENGOBATAN PENYAKIT KRONIS - Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2026)
The application of nanomedicine technology in the treatment of chronic diseases shows a very promising potential to revolutionise conventional therapeutic approaches. Through their ability to improve drug bioavailability, more precise targeting, and controlled drug delivery, nanomedicines open up new opportunities in the management of chronic diseases such as cancer, diabetes, and cardiovascular diseases. The advantages of nanomedicines in overcoming biological barriers, improving drug efficacy, and reducing side eflects provide new hope for patients suflering from chronic diseases that have been difficult to treat with conventional methods. However, despite its great potential, the application of nanomedicines still faces significant challenges. Long-term safety issues, complexity in production and regulation, and high development costs are still major barriers to the widespread adoption of this technology. Further research, multidisciplinary collaboration, and the development of a comprehensive regulatory framework are required to overcome these challenges. With continued eflorts in overcoming the existing barriers, nanomedicine has the potential to transform the landscape of chronic disease treatment, oflering more eflective and personalised solutions to millions of patients worldwide.